Sistem Monitoring Hasil Pemanenan Madu Berbasis IoT - Rusito; Doni Marhab Prakoso Gasta Wijaya (Elkom: Jurnal Elektronika dan Komputer, 2023)
Honey is a natural liquid that contains a lot of sugar produced by bees (genus Apis) from flower nectar and has a sweet taste. Honey contains a multitude of benefits that are good for the body, including being a source of nutrients, improving body metabolism, anti-bacterial, and others. The purpose of designing the Honey Harvest Monitoring System with ARDUINO-based IOT is to help breeders maximize honey harvesting results. This study aims to design an intelligent system for controlling the temperature in bee hives, humidity in bee hives, and monitoring honey yields, measuring the temperature and humidity of the storage room using DHT 11 sensors, and monitoring honey harvest time using Load Cell sensors. The temperature and humidity controller in the cage uses a blower/fan. Sensor data will be processed using the Wemos D1 R1 microcontroller and then sent to an Android application via the internet network using a real-time Firebase database so that it can be accessed anywhere and anytime. The way this system works is that if the room temperature is >38 degrees Celsius, the blower/fan will turn on, and will turn off if the temperature is 40%, the artificial window will open and will close if the humidity is